Crise do alojamento estudantil em Portugal: Análise da opinião pública em redes sociais - Daniela Sofia Neto; Raquel Ribeiro (Cidades, Comunidades e Território)
Student accommodation has not been left out of the housing crisis that is affecting the country. The start of the 2022/2023 academic year saw difficulties in accessing student accommodation arising due to the significant decrease in private accommodation available for rent and the increase in rent values. With the aim of identifying lay theories about the problem and about the proposals presented by political parties and student associations for its resolution, an exploratory study was carried out based on the identification of news on the subject and the analysis of comments published on them in social media. The results of the thematic analysis carried out on the 2312 comments published between September and December 2022 show that this is a recurring problem that is worsening due to the insufficiency of the existing public offer. Results highlight structural causes, such as the functioning of the market and the role of the State, but also contextual causes such as touristification and the attraction of foreign students and residents. The results also show a polarization of positions, namely through the mobilization of negative stereotypes. It concludes highlighting the importance of articulating the different public polices and discussing the relationship between the student accommodation crisis and the housing crisis that the country is experiencing in the reproduction of social inequalities.